Stuck in a trap? Long-term unemployment under two-tier unemployment compensation schemes - Wolfgang Nagl; Michael Weber (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
We empirically investigate how two-tier unemployment compensation schemes affect the profile of re-employment hazards. We exploit the aggravation of an existing two-tier scheme in Germany in 2005 and estimate its impact on re-employment rates at different durations. For the short-term unemployed, the hazard rate increases and negative duration dependence declines. For the long-term unemployed, we find none and for certain groups of job seekers even negative impacts on the re-employment hazard. Our results indicate that two-tier unemployment compensation schemes might create a long-term unemployment trap: If employers rank applicants by their duration in unemployment, incentivizing all job seekers to exert higher search efforts may reduce the reemployment probabilities for the long-term unemployed.
Keywords: J64; J65; J68; 330; Unemployment insurance; two-tier unemployment compensation; unemployment duration; re-employment rate; Hartz reforms.